Eplerenone Prevents Cardiac Fibrosis by Inhibiting Angiogenesis in Unilateral Urinary Obstruction Rats - Chang, Yi; Ben, Ying; Li, Hui; Xiong, Yunzhao; Chen, Gege; Hao, Juan; Ma, Xuelian; Gao, Xiaomeng; Qiang, Panpan; Shimosawa, Tatsuo; Wang, Xiangting; Yang, Fan; et al. (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Introduction. Cardiovascular disease constitutes the leading cause of mortality in patients with chronic kidney disease (CKD), which is termed cardiorenal syndrome type 4 (CRS-4). Here, we report the development of pathological cardiac remodeling and fibrosis in unilateral urinary obstruction (UUO) rats. Methods. Hematoxylin and eosin (H&E) staining was performed to observe the pathology of myocardial tissue. The degree of myocardial tissue fibrosis was observed by Masson and Sirius red staining. Immunohistochemical staining was applied to detect the expression of CD34 and CD105 in myocardial tissue, and immunofluorescent staining was performed to examine the expression of CD34, collagen I/collagen III, and alpha smooth muscle actin (α-SMA). The expression of the signal pathway-related proteins vascular endothelial growth factor A (VEGFA), vascular endothelial growth factor receptor 2 (VEGFR2), nuclear factor κB (NF-κB), and interleukin (IL)-1β was tested by western blotting. Reverse transcription-polymerase chain reaction (RT-PCR) was used to detect the mRNA levels of serum and glucocorticoid-inducible kinase (SGK)-1, NF-κB, and interleukin-1β (IL-1β). Results. The results showed the development of pathological cardiac remodeling and cardiac dysfunction in UUO rats. Moreover, there was more angiogenesis and endothelial-mesenchymal transition (End-MT) in the UUO group, and these effects were inhibited by eplerenone. Conclusions. The results indicated that this cardiac fibrosis was associated with angiogenesis and that End-MT was related to aldosterone and mineralocorticoid receptor (MR) activation. Moreover, in association with the MR/IL-1β/VEGFA signaling pathway, early treatment with the MR antagonist eplerenone in rats with UUO-induced CKD may significantly attenuate MR activation and cardiac fibrosis.